Correction to: Salivary glands in workers of Ruptitermes spp. (Blattaria, Isoptera, Termitidae, Apicotermitinae): a morphological and preoteomic approach (Cell and Tissue Research, (2021), 10.1007/s00441-021-03469-w) - Costa‑Leonardo, Ana Maria [UNESP]; da Silva, Iago Bueno [UNESP]; Janei, Vanelize [UNESP]; Poiani, Silvana Beani [UNESP]; dos Santos‑Pinto, José Roberto Aparecido [UNESP]; Esteves, Franciele Grego [UNESP]; Palma, Mario Sérgio [UNESP] (Springer Nature, 2021)
A correction to this paper has been published: https://doi.org/10.1007/s00441-021-03475-y.